2019
DOI: 10.4067/s0717-75182019000500593
|View full text |Cite
|
Sign up to set email alerts
|

Importancia nutricional y actividad biológica de los compuestos bioactivos de quelites consumidos en México

Abstract: Este trabajo fue recibido el 07 de julio de 2018. Aceptado con modificaciones: 03 de enero de 2019.Aceptado para ser publicado: 15 de abril de 2019.RESUMEN Sólo un 30% de los hogares en México, presentan seguridad alimentaria, es decir, un gran porcentaje de los hogares y por ende de la población no satisfacen las necesidades básicas diarias de macro y micronutrimentos. Los quelites, que se definen como plantas silvestres comestibles (hojas, tallos y flores) son una fuente accesible, continua, económica y adec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
(46 reference statements)
0
12
0
1
Order By: Relevance
“…The traditional Mexican diet may be of great interest because it includes the highest number of endemic plants. Between 20% and 30% of plant species in Mexico contribute to the basic diet of low-income populations [1,2]. Chenopodium spp., Suaeda torreyana, Portulaca oleracea, and Porophyllum spp.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional Mexican diet may be of great interest because it includes the highest number of endemic plants. Between 20% and 30% of plant species in Mexico contribute to the basic diet of low-income populations [1,2]. Chenopodium spp., Suaeda torreyana, Portulaca oleracea, and Porophyllum spp.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, according to Hervert-Hernández et al [55], the inclusion of fruits, vegetables, even roots, stems, and leaves contributes to high consumption of antioxidants, and therefore improves to the diet quality. However, nowadays the importance of consuming these potential sources of phytochemicals such as quelites has been forgotten, which could be used as alternative therapies to reduce the effects of various pathophysiological conditions, including As toxicity [21]. Some studies on populations exposed to As have reported that the consumption of natural supplements or foods rich in bioactive compounds improve the processes of methylation and increase the levels of excretion of As, promoting an efficient recovery process [28,42,53,56].…”
Section: Uas Concentrationmentioning
confidence: 99%
“…On the other hand, other nutrients and compounds have been reported as beneficial, such as dietary fiber, carotenoids, and organic acids present in parts of plants and vegetables which reduce the toxic effects of heavy metals, including As [21,28,42]. Moreover, another study showed that low diets in green leafy vegetables and micronutrients such as calcium, folates, and vitamin C increase the probability of presenting toxic effects characteristic of As [57].…”
Section: Uas Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Mexico, approximately 2168 different food species, not solely quelites, have been recorded based on ethnobotanical studies of useful plants, but the proximate analysis and protein, amino acid and bioactive compound profiles are available for fewer than 30 species, including those of the genera Amaranthus , Begonia , Chenopodium , Cyclanthera , Erythrina , Sechium , Cucurbita , Xanthosoma , Phaseolus and Phytolacca [ 17 ]. Species with edible stems and leaves stand out in their supply of micronutrients to alleviate nutritional deficiencies, mainly in children and pregnant women, and prevent chronic diseases [ 18 , 19 ]. Guil-Guerrero [ 20 ] noted that, in addition to documenting the nutritional composition of wild plants, their cytotoxic, allergic or poisonous effects should be studied.…”
Section: Introductionmentioning
confidence: 99%